Evaluating the Radiation and Temperature Effect on Photovoltaic Systems - Sobhan Dorahaki (Bulletin of Electrical Engineering and Informatics, 2015)
One of the best ways to identify and design a system is simulating and to achieve this goal, we use simulation software such as MATLAB Simulink. In this study, the relations ruling photovoltaic is described. Then, on the relations basis, a photovoltaic system is simulated in MATLAB software. After photovoltaic system simulation, regardless the specific geographic area, radiation and temperature effect on photovoltaic system is generally simulated. Finally, with regard to radiation and temperature values effect on, it was concluded that we overlook the temperature effect than radiation effect on photovoltaic system designing. It certainly does not mean overlooking the temperature effect. It means a low-effect power changes per temperature changes against radiation.